THE EFFECTS OF USING L1 TRANSLATION ON YOUNG LEARNERS’ FOREIGN LANGUAGE VOCABULARY LEARNING - Codina Camó, Aïda; Pladevall Ballester, Elisabet (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In the field of foreign language (FL) vocabulary acquisition, there seems to be a growing awareness of the fact that the mother tongue (L1) might have a facilitating role for language learners. Research has found evidence to support the positive effects of using the L1 as an instructional tool, particularly at the initial stages of FL learning. The present study explores the role that the L1 plays in young learners’ retention of and access to English vocabulary. An experimental group and the corresponding control group of 10-11 year-old children in an EFL Catalan school context were recruited for the study. The experimental group was exposed to both the English input and the L1 translation of the target items, whereas the control group received just the English input. Differences between the groups in terms of lexical retention and lexical access were analysed. Results of the present study suggest that providing students with the lexical items results in learners retaining more lexical items, accessing them with greater ease and recalling them for longer periods of time. Resumen En el campo del aprendizaje del vocabulario de una lengua extranjera, parece haber cada vez más conciencia del hecho que la lengua materna (L1) podría tener un papel facilitador para los aprendices de una lengua extranjera. La investigación ha evidenciado los efectos positivos del uso de la L1 como una herramienta de instrucción, sobre todo en las etapas iniciales del aprendizaje de la lengua extranjera. Éste estudio explora el papel que desempeña la L1 en la retención y el acceso del vocabulario inglés en estudiantes jóvenes. Para el presente estudio, se reclutaron un grupo experimental y el correspondiente grupo control de niños de 10-11 años escolarizados en un contexto en el que, siendo el catalán la lengua materna de los estudiantes, el inglés se enseña como lengua extranjera. El grupo experimental fue expuesto al input en inglés y a la traducción del vocabulario y, en contra partida, el grupo control solo recibió el input en inglés. Los resultados de éste estudio muestran que proveer a los estudiantes con la traducción del vocabulario hace que los alumnos retengan más elementos léxicos, accedan a ellos con mayor facilidad y los recuerden por períodos más largos de tiempo.